Investigations on thin SS sheets joining by pulsed micro-plasma transferred arc process. Issue 1 (May 2019) - Chaudhary, Jigar; Jain, Neelesh Kumar; Pathak, Sunil; Koria, S. C.
Abstract: Joining of thin sheets is challenging due to difficulty in maintaining localized melting and solidification. This becomes more difficult while thin sheet joining of stainless steel due to its poor weld/joining properties. This article reports on autogenous joining of 0.4 mm thickness sheets of 316L austenitic stainless steel (SS) using pulsed micro-plasma transferred arc (P-µPTA) process. Decision of using autogenous joining was taken on the basis of observations of experimentation on homogenous joining of SS thin sheets using 0.274 mm diameter SS filler wire. Effects of pulse-on time, pulse-off time, peak current and torch travel speed on the joint strength of weld were investigated with an objective to identify the optimum values for the maximum tensile strength of the joint. It was found that 50% duty cycle, 10% pulse frequency, 3.5 A peak current and torch travel speed 250 mm/min yielded maximum joint strength 553 MPa. The fusion zone was found to have finer grain size. Non-existence of heat-affected zone absence was assured by very minor dissimilarity in the values of microhardness over the fusion zone. This study establishes the capability of pulse micro-plasma transferred arc process for joining thin sheets of stainless steel without any filler material and producing very good quality joint with very insignificant heat-affected zone (HAZ), thermal distortion and porosity using much less power as compared to conventional fusion joining processes.